Enhancement of anti-inflammatory and antioxidant activities of prickly pear fruits by high hydrostatic pressure: A chemical and microstructural approach. (June 2019) - Gómez-Maqueo, Andrea; García-Cayuela, Tomás; Welti-Chanes, Jorge; Cano, M. Pilar
Abstract: Prickly pears were submitted to high hydrostatic pressure (HHP) (pressure: 100, 350 and 600 MPa; temperature: 17–34 °C; time: come-up time (CUT) and 5 min) to enhance their health potential by increasing the extractability of bioactive compounds. Phenolics, betalains and ascorbic acid were analyzed by high performance liquid chromatography (HPLC) and spectrophotometry in peels and in pulps to determine their contribution to in-vitro bowel-related antioxidant (oxygen radical absorbance capacity; ORAC) and anti-inflammatory activities (hyaluronidase inhibition and nitric oxide radical scavenging activity). Antioxidant activity in Pelota and Sanguinos pulps increased 81.1 and 68.2% at 350 MPa/5 min, respectively, and correlated with the increase of phenolic acids, isorhamnetin glucosyl-rhamnosyl-rhamnoside (IG1) and isorhamnetin glucosyl-rhamnoside (IG5). Anti-inflammatory activity increased 85.7 and 117.5% in Pelota and Sanguinos pulps, respectively, at 600 MPa/CUT and correlated with the increase of isorhamnetin glucosyl-rhamnosyl-pentoside (IG2), isorhamnetin glucosyl-pentoside (IG4) and IG5. Industrial relevance: Prickly pears are potential sources of low-cost functional foods because they are rich in valuable bioactive compounds. However, these are only partially bioaccessible because they compartmentalized within cellular structures and bound to cell walls. By processing with high hydrostatic pressure, we can obtain fruit products with a higher bioactive content. This potentially enhances bowel-related antioxidant and anti-inflammatory activities. These results take us one step closer to the prevention of chronical diseases with the consumption of our everyday foods. The use of non-thermal technologies for the enhancement of health potential in vegetable foods could result in a useful tool for the development of the novel foods of the 21st century. Highlights: Phenolic increments enhanced antioxidant and anti-inflammatory activities. Bioactive increases after 5 min were achieved by stability during CUT. Pressurization effects were different on peel and pulp microstructure. Intercellular space loss and cell wall rupture increased extractability of bioactives.